Development of anaerobic function during childhood and adolescence - Praagh, E. V. (Pediatric Exercise Science, 2000)
This review summarizes the research relating anaerobic function to growth among children and adolescents. Pediatric practitioners and scientists are always struck by the impressive accumulation of results relating to the cardiopulmonary system. However, anaerobic fitness has received much less research attention. This is surprising, considering that high-intensity exercises lasting only a few seconds is a more ÒnaturalÓ pattern during growth than prolonged low-intensity exercises. In anaerobic tasks or sport events such as sprint running, sprint swimming, sprint cycling, jumping, or throwing, the childÕs performance is distinctly lower than that of the adult. This partly reflects the childÕs lesser ability to generate mechanical energy from chemical energy sources during short-term intensive work or exercise. Because both intramuscular high energy phosphate kinetics and muscle cross-section vary during growth and maturation, this review examines some developmental aspects of energetic- and mechanical factors involved in anaerobic performance. Anaerobic muscle function and performance are quantitative traits influenced by several determinants such as genetic factors, age and gender, muscle fiber characteristics, hormonal and training factors. Because of ethical and methodological constraints when investigating healthy children, this review also includes fundamental work done on some animal models. The Anaerobic Paradox The children spontaneously choose varied exercises, they readily strain themselves maximally for some seconds but heartily dislike monotonous, heavy work. Their way of living is rather of an anaerobic character.